Pollination compatibility of Dendrobium spp. orchids from Bali, Indonesia, and the effects of adding organic matters on seed germination under in vitro culture - IDA AYU PUTRI DARMAWATI; IDA AYU ASTARINI; HESTIN YUSWANTI; YUYUN FITRIANI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Darmawati IAP, Astarini IA, Yuswanti H, Fitriani Y. 2021. Conservation of Dendrobium spp. Bali orchids (Indonesia) through in vitro seed culture. Biodiversitas 22: 2554-2559. Orchid species, including Dendrobium spp., originated from Bali are threatened to extinction due to habitat destruction, illegal hunting, small population size, and the effects of global environmental change. Conservation strategies are therefore required to preserve the remaining germplasm, one of which is through in vitro seed propagation. This research aimed to investigate the pollination compatibility (i.e., pollination that produce fruits) of Dendrobium orchids originated from Bali, and to determine the effects of adding organic matters (i.e., coconut water, tomato extract, and peptone) to the base media on orchid seed germination under in vitro culture condition. Self-pollination and sibling pollination were implemented to seven orchid species, namely Dendrobium macrophyllum, D. heterocarpum, D. fimbriatum, D. linearifolium, D. spathilingue, D. secundum, and D. plicatile. The results showed that only four species, i.e., D. macrophyllum, D. heterocarpum, D. fimbriatum, and D. linearifolium, that produced fruits after being pollinated. The subsequent in vitro propagation of seeds produced by the four species showed that the addition of organic matters of tomato extract, coconut water, and peptone significantly affected the germination of Dendrobium forma Bali orchid seeds, indicated by different germination rates. The addition of 20% coconut water to Vacin and Went (VW) media gave the highest percentages of seed germination and protocorm formation for D. macrophyllum, D. heterocarpum, and D. fimbriatum at 98.33% and 95.00%; 91.67% and 91.67%; and 95% and 98.33%, respectively. Our findings can serve as baseline information when developing conservation strategies of Dendrobium orchids from Bali, particularly from the aspect of propagation